The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/aenm.201902106
|View full text |Cite
|
Sign up to set email alerts
|

A Disquisition on the Active Sites of Heterogeneous Catalysts for Electrochemical Reduction of CO2 to Value‐Added Chemicals and Fuel

Abstract: Renewable‐electricity‐powered electrocatalytic CO2 reduction reactions (CO2RR) have been identified as an emerging technology to address the issue of rising CO2 emissions in the atmosphere. While the CO2RR has been demonstrated to be technically feasible, further improvements in catalyst performance through active sites engineering are a prerequisite to accelerate its commercial feasibility for utilization in large CO2‐emitting industrial sources. Over the years, the improved understanding of the interaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
104
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 356 publications
(635 reference statements)
0
104
0
Order By: Relevance
“…Among them, ZnN 4 on microporous N-doped carbon (SA-Zn/MNC) derived from ZIF-8 exhibited the highest activity and selectivity for CH 4 production (Figure 11). [14] The FE for CH 4 For heterogeneous molecular catalysts, Weng et al [107a] revealed the catalytic mechanism of Cu phthalocyanine supported on CNT involves the reversible structural and oxidation state changes of Cu atoms to form ≈2 nm Cu clusters as the active sites for methane production. As confirmed by in situ XAS analysis, a similar phenomenon was not observed on the Cu based MOF or complexes with a nonconjugated ligand.…”
Section: Production Of Methanementioning
confidence: 99%
See 1 more Smart Citation
“…Among them, ZnN 4 on microporous N-doped carbon (SA-Zn/MNC) derived from ZIF-8 exhibited the highest activity and selectivity for CH 4 production (Figure 11). [14] The FE for CH 4 For heterogeneous molecular catalysts, Weng et al [107a] revealed the catalytic mechanism of Cu phthalocyanine supported on CNT involves the reversible structural and oxidation state changes of Cu atoms to form ≈2 nm Cu clusters as the active sites for methane production. As confirmed by in situ XAS analysis, a similar phenomenon was not observed on the Cu based MOF or complexes with a nonconjugated ligand.…”
Section: Production Of Methanementioning
confidence: 99%
“…[ 3 ] Based on different catalysts and reaction pathways, more than 16 different products have been obtained, such as CO and HCOOH via a two‐electron process, HCHO via a four‐electron process, CH 4 via an eight‐electron process, as well as multicarbon (C 2+ ) products (e.g., ethylene and ethanol) via CC coupling. [ 4 ] The reduction process is further complicated due to the competing hydrogen evolution reaction (HER), which has similar equilibrium potentials in aqueous electrolytes to the CO 2 RR (Equation ). As a result, the synthesis of an ideal catalyst with high selectivity for a specific product except CO is still a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[114] This renewable-electricity-powered CO 2 RR can reduce CO 2 into value-added fuels and chemicals such as formic acid (HCOOH), methanol (CH 3 OH), methane (CH 4 ), ethylene (C 2 H 4 ), and carbon monoxide (CO). [115] MXenes, as a class of promising electrocatalyst materials, have been used in CO 2 RR because of their high conductivity, tunable surface groups, and multiple binding sites. [25,48,56,116] Hiring theoretical calculations to predict the performance of transition metal (Group IV, V, VI) carbide M 3 C 2 , Li et al [25] found that Mo 3 C 2 and Cr 3 C 2 were the two best catalyst candidates for the highly selective conversion of CO 2 to CH 4 .…”
Section: Carbon Dioxide Reduction Reactionmentioning
confidence: 99%
“…In addition, CO 2 methanation provides an alternative way to H 2 storage by formation of synthetic natural gas, which is also attractive in the power‐to‐gas technology. [ 5 ] The approaches of CO 2 conversion can be classified as four categories: biochemical method, [ 6 ] thermochemical method, [ 7 ] photochemical method, [ 8 ] and electrochemical method. [ 1,9 ] Among them, electrochemical reduction reaction (CO 2 RR) is treated as promising technology because it can be conducted under mild conditions in aqueous solution, in which water instead of molecular H 2 gas is employed as hydrogen source.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CO 2 methanation provides an alternative way to H 2 storage by formation of synthetic natural gas, which is also attractive in the power-to-gas technology. [5] The approaches of CO 2 conversion can be classified as four categories: biochemical…”
mentioning
confidence: 99%